BACTERICIDAL EFFECTIVENESS OF FREEZE-CAST CERAMIC FILTERS IMPREGNATED WITH SILVER NANOPARTICLES - Amadio,T. de M. (2018)
ABSTRACT This work aimed to produce freeze-cast pellets of porous ceramic filters of alumina and kaolinite impregnated with silver nanoparticles and to test the efficiency of bactericidal effects. Silver nanoparticles were characterized by average particle size, zeta potential and TEM. After impregnation, leached water was analyzed by graphite furnace atomic absorption spectrometry (GFAAS) that showed an efficiency of more than 99.9% in silver impregnation. From SEM/EDS, it was possible to observe that the pellets have a homogeneous distribution of silver nanoparticles. A halo of inhibition detected by the disc diffusion test shows a strong bactericidal effect of the filters.